β-arrestin-2-biased agonism of delta opioid receptors sensitizes transient receptor potential vanilloid type 1 (TRPV1) in primary sensory neurons - Rowan, Matthew P (BioMed Central, 2014)
Despite advances in understanding the signaling mechanisms involved in the development and maintenance of chronic pain, the pharmacologic treatment of chronic pain has seen little advancement. Agonists at the mu opioid receptor (MOPr) continue to be vital in the treatment of many forms of chronic pain, but side-effects limit their clinical utility and range from relatively mild, such as constipation, to major, such as addiction and dependence. Additionally, chronic activation of MOPr results in pain hypersensitivity known as opioid-induced hyperalgesia (OIH), and we have shown recently that recruitment of β-arrestin2 to MOPr, away from transient potential vanilloid eceptor type 1 (TRPV1) in primary sensory neurons contributes to this phenomenon. The delta opioid receptor (DOPr) has become a promising target for the treatment of chronic pain, but little is known about the effects of chronic activation of DOPr on nociceptor sensitivity and OIH. Here we report that chronic activation of DOPr by the DOPr-selective agonist, SNC80, results in the sensitization of TRPV1 and behavioral signs of OIH via β-arrestin2 recruitment to DOPr and away from TRPV1. Conversely, chronic treatment with ARM390, a DOPr-selective agonist that does not recruit β-arrestin2, neither sensitized TRPV1 nor produced OIH. Interestingly, the effect of SNC80 to sensitize TRPV1 is species-dependent, as rats developed OIH but mice did not. Taken together, the reported data identify a novel side-effect of chronic administration of β-arrestin2-biased DOPr agonists and highlight the importance of potential species-specific effects of DOPr agonists.